Efficacy of synbiotic treatment in children with acute rotavirus diarrhea - Made Ratna Dewi; Yati Soenarto; I Putu Gede Karyana (Indonesian Pediatric Society, 2015)
Background Diarrhea is one of the major causes of morbidityand mortality in children throughout the world, mostly due torotavirus infection. In daily practice, we routinely use the WorldHealth Organization Five steps for managing acute diarrhea.Thispractice has shown great success in diarrhea management, butconcerns remain on reducing the duration of diarrhea to preventcomplications. Synbiotics can reduce the severity of diarrhea.However, there has been limited data on synbiotic therapy fortreating acute rotavirus diarrhea in children.Objective To compare the durations of acute rotavirus diarrheatreated with synbiotics vs. placebo.Methods This study was a randomized, double-blind, clinical trial,performed at the Pediatric Gastrohepatology Division, Sanglahand Wangaya Hospitals in Denpasar. Subjects were children aged6 to 59 months with acute rotavirus diarrhea. Rotavirus wasdiagnosed by immune chromatography assay. The synbiotic groupreceived probiotic comprised of Lactobacillus sp., Streptococcus sp.,Bifidobacterium sp. (total viable count 1.00x109 CFU per dose), andprebiotic consisted of 990.00 mg fructooligosacharide (FOS). Theplacebo consisted of lactose monohydrate packaged similarly as thesynbiotics. Subjects orally ingested 1 pack per day for 5 days.Results Seventy children with acute rotavirus diarrhea wasinvolved in this study. The median duration of diarrhea in thesynbiotic group was 50.0 (SE 1.1); 95%CI 47.9 to 52.1 hours, whilethat of the placebo group was 63.0 (SE 5.9); 95%CI 51.4 to 74.6hours. Based on Kaplan-Meier survival analysis, the duration ofdiarrhea in the synbiotic group was significantly shorter than thatof the placebo group (log-rank test P <0.0001).Conclusion In children with acute rotaviral diarrhea, synbioticreduces the duration of diarrhea compared to placebo.